High Interfacial Hole‐Transfer Efficiency at GaFeO3 Thin Film Photoanodes. Issue 45 (22nd October 2020) - Sun, Xin; Tiwari, Devendra; Fermin, David J.
Abstract: The photoelectrochemical properties of polycrystalline GaFeO3 (GFO) thin films are investigated for the first time. Thin films prepared by sol–gel methods exhibit phase‐pure orthorhombic GFO with the Pc 21 n space group, as confirmed by X‐ray diffraction and Raman spectroscopy. Optical responses are characterized by a 2.72 eV interband transition and sub‐bandgap d–d transitions associated with octahedral and tetrahedral coordination of Fe 3+ sites. DFT‐HSE06 electronic structure calculations show GFO is highly ionic with very low dispersion in the valence band maximum (VBM) and conduction band minimum (CBM). Electrochemical impedance spectroscopy reveals n‐type conductivity with a flat band potential ( U fb ) of 0.52 V versus reversible hydrogen electrode, indicating that GFO has the most positive CBM reported of any ferrite. The photoelectrochemical oxidation of SO3 2− shows an ideal semiconductor–electrolyte interfacial behavior with no evidence of surface recombination down to the U fb . Surprisingly, the onset potential for the oxygen evolution reaction also coincides with the U fb, showing interfacial hole‐transfer efficiency above 50%. The photoelectrochemical properties are limited by bulk recombination due to the short‐diffusion length of minority carriers as well as slow transport of majority carriers. Strategies towards developing high‐efficiency GFO photoanodes are briefly discussed. Abstract : The photoelectrochemical oxygen evolution reaction (OER) at semiconductor electrodes is a highly complex multielectron transfer process that commonly requires large potential bias to minimize competing interfacial recombination losses. Herein, for the first time, it is shown that polycrystalline GaFeO3, a highly ionic n‐type ferrite with very positive band edges, can promote the OER without external bias.